PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP PEMAHAMAN KONSEP MATEMATIK MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA STKIP PGRI SUMBAR - Anggraini, Villia (Universitas Ahmad Dahlan, 2012)
Understanding of concepts, of students not optimal while learning process in math department caused by less variation of teaching method. The effort to solve these problem by using cooperative learning model. The purpose of this research was to know the students: 1) understanding of consept, communication ability, problem solving of math students follow learning cooperative learning model type STAD better than understanding of concept, communication ability, problem solving ability of students attending a convensional learning.This research imposition made STKIP PGRI Padang students taking courses in Ordinary Differential Equations 2010/2011 academic year. Experimental research done to compare two treatment through sample class. Data were collected through the test results of study and observation. Results of analysis of data showed that Understanding math concepts students attending a model of cooperative learning type STAD better than understanding of math concepts of students attending conventional.